Single-centre experience of primary cutaneous Merkel cell carcinoma of the head and neck between 1996 and 2014. Issue 7 (September 2016) - Patel, Muneer; Newlands, Carrie; Whitaker, Stephen
Abstract: We retrospectively reviewed the management at our centre of 25 patients with Merkel cell carcinoma (MCC) of the head and neck. We obtained details of the operation, including wide local excision, sentinel lymph node biopsy (SNB), neck dissection, postoperative radiotherapy, and clinical outcomes, from patients' records. All patients were white, 11 were men and 14 women, mean age at presentation 81 years (range 67-90). At the time of diagnosis, 18 patients had stage I disease, and 7 stage II disease. Twenty had wide local excision and radiotherapy, and 5 had wide local excision alone. Wide local excision and radiotherapy are successful treatments. In patients with no sign of metastases, SNB at the time of excision is a well-researched option and should be considered the gold standard of care.